RANCANG BANGUN APLIKASI KALKULATOR GIZI BERBASIS ANDROID (Information Technology and Telematics, 2016)
Abstract – Android operating system which offers a variety of interesting applications are still much in demand in the community. One is the use of applications in the android smartphone associated with the health of the world one of which is on the nutritional status, a person to know the nutritional status by calculating the body mass index (BMI) to determine the outcome then someone will know the nutritional status they are in which category and what diseases can arise if it is in the category. Applications android-based nutrition calculator is an example. This application is built using the Java programming language and XML, the Eclipse editor. This application uses the BMI formula applied in coding a program that will calculate BMI and the results of the count are connected in a database. The purpose of this application is made by utilizing the features of this android smartphone then it will certainly be easier and faster to someone who will find out their nutritional status. Keywords: nutritional status, nutrition, IMT, android Abstrak – Sistem operasi android yang menawarkan berbagai jenis aplikasi menarik masih banyak diminati di masyarakat. Salah satunya adalah penggunaan aplikasi di smartphone android yang berhubungan dengan dunia kesehatan salah satunya adalah mengenai status gizi, seseorang untuk mengetahui status gizinya dengan cara menghitung indeks massa tubuh (IMT) dengan mengetahui hasilnya maka seseorang akan mengetahui status gizi mereka berada pada kategori yang mana dan penyakit apa yang dapat muncul jika berada pada kategori tersebut. Aplikasi kalkulator gizi berbasis android ini contohnya. Aplikasi ini dibuat menggunakan bahasa pemrograman Java dan XML, dengan editor Eclipse. Aplikasi ini menggunakan rumus IMT yang diterapkan dalam coding program yang akan menghitung IMT dan hasil hitungan dikoneksikan dalam database.  Tujuan aplikasi ini dibuat dengan memanfaatkan fitur smartphone android ini maka tentunya akan lebih mudah dan cepat untuk seseorang yang akan mengetahui status gizi mereka. Kata Kunci : status gizi, gizi, imt, android.